Areolar lymphocytoma in a child: A rare cutaneous presentation of borreliosis. Issue 1 (4th December 2017) - Ogimi, Chikara; Crowell, Claudia; Boos, Markus D.
Abstract: Lyme disease is a common tick‐borne infection caused by Borrelia burgdorferi in the United States, where infection is most prevalent in the northeastern and mid‐Atlantic states. Although classically associated with erythema migrans, Lyme disease caused by Borrelia species found in Europe may also present with other cutaneous findings. Here we report the case of a girl who was clinically diagnosed with Lyme disease based on her history of recent travel and the appearance of an areolar lymphocytoma; this was confirmed by testing. Testing for European Lyme disease does not follow the testing algorithm that the Centers for Disease Control and Prevention recommends and may be easily missed. Our case serves as an important reminder that common infections can have varying presentations depending on their region of acquisition and may require specialized testing for accurate diagnosis.